Prospects of modeling poststroke epileptogenesis. Issue 4 (25th July 2016) - Reddy, Doodipala Samba; Bhimani, Aamir; Kuruba, Ramkumar; Park, Min Jung; Sohrabji, Farida
Abstract : This Review describes the current status of poststroke epilepsy (PSE) with an emphasis on poststroke epileptogenesis modeling for testing new therapeutic agents. Stroke is a leading cause of epilepsy in an aging population. Late‐onset "epileptic" seizures have been reported in up to 30% cases after stroke. Nevertheless, the overall prevalence of PSE is 2–4%. Rodent models of stroke have contributed to our understanding of the relationship between seizures and the underlying ischemic damage to neurons. To understand whether acutely generated stroke events lead to a chronic phenotype more closely resembling PSE with recurrent seizures, a limited variety of approaches emerged in early 2000s. These limited methods of causing an occlusion in mice and rats show different infarct size and neurological deficits. The most often employed procedure for inducing focal ischemia is the middle cerebral artery occlusion. This mimics the pathophysiology seen in humans in terms of extent of damage to cortex and striatum. Photothrombosis and endothelin‐1 models can similarly evoke episodes of ischemic stroke. These models are well suited to studying mechanisms and biomarkers of epileptogenesis or optimizing novel drug discoveries. However, modeling of PSE is tedious, is highly variable, and lacks validity; therefore, it is not widely implemented in epilepsy research. Moreover, the relevance of ischemic models to specific forms of human stroke remains unclear. Stroke modeling in young male rodents lacks clinical relevance to elderly populations and especially to women, likely as a result of sex differences. Nevertheless, because of the neuronal damage and epileptogenic insult that these models trigger, they are helpful tools in studying acquired epilepsy and prophylactic drug therapy. © 2016 Wiley Periodicals, Inc. Abstract :